Optimization of Drip Irrigation System to Improve Water Use Efficiency and Tomato Crop Productivity - Mulianda, Pratiwi; Damanik, Annisa Purnamasari; Surya, Satria Adi (ITScience (Information Technology and Science), 2025)
This literature review explores the optimization of drip irrigation systems to improve water use efficiency (WUE) and tomato crop productivity, particularly under dryland conditions. Four key studies were analyzed, focusing on hydraulic performance, integrated technologies, and agronomic outcomes. Sharu and Razak (2020) demonstrated that hydraulic modeling using EPANET achieved excellent water emission uniformity (CU and EU > 95%) with potential for energy savings through optimized pump power. Nurazila and Anggraini (2022) reported that drip irrigation significantly enhanced vegetative growth and WUE compared to manual irrigation. Suvitha et al. (2021) highlighted that drip fertigation with medium frequency and high NPK dosage maximized yield and WUE in sandy soils. Ramakrishna et al. (2024) found that combining drip irrigation with black plastic mulch resulted in the highest plant growth, fruit yield, and WUE by reducing evaporation. Collectively, the findings confirm that integrating supporting technologies—such as hydraulic modeling, fertigation, and mulching—can significantly enhance drip irrigation efficiency, conserve water, and improve tomato productivity, offering strong potential for adoption in water-limited agricultural regions.